Age-Dependent Decrease in the Induction of Regulatory T Cells Is Associated With Decreased Expression of RALDH2 in Mesenteric Lymph Node Dendritic Cells - Takano, Tomohiro; Kotaki, Ryutaro; Park, Jihyun; Yoshida, Tadashi; Wakatsuki, Yoshio; Tanokura, Masaru; Miyakawa, Takuya; Takahashi, Kyoko; Nakajima-Adachi, Haruyo; Hachimura, Satoshi (Frontiers in Immunology, 2020)
A decline in immune function with aging has been reported. Regulatory T cell (Treg) induction is known to decrease with age, and elucidating the underlying mechanism is important for preventing age-related diseases due to age-related chronic inflammation. In the intestine, dendritic cells (DCs) play an important role in inducing Tregs specific to oral antigens, and they efficiently induce Tregs via production of retinoic acid (RA), a vitamin A metabolite, catalyzed by the enzyme retinaldehyde dehydrogenase 2 (RALDH2). We have previously reported that in the mesenteric lymph node (MLN), a secondary lymphoid tissue in which immune responses to oral antigens are induced, four DC subsets express different levels of CD11b, CD103, and PD-L1, and we have reported that the CD11b-CD103+PD-L1high subset expresses the highest levels of the RALDH2 gene and induces Tregs in vitro. We examined Treg induction in young and aged mice using a Treg induction model by administering a food antigen, and we found that antigen-specific Treg induction was decreased in aged mice. We further investigated the MLN DCs, and a significant decrease in RALDH2 gene expression was observed in MLN DCs from aged mice. As factors, we found that the proportion of the CD11b-CD103+PD-L1high subset was decreased in aged mice compared with that in young mice and that RALDH enzyme activity was decreased in the CD11b-CD103+PD-L1high and CD11b+CD103+PD-L1high subsets. Furthermore, analysis of the methylation of the RALDH2 gene promoter region revealed that CpG motifs were more methylated in the MLN DCs of aged mice, suggesting that RALDH2 expression was suppressed by epigenetic changes. Finally, we found that RA treatment tended to increase Treg induction. These results suggest that the regulation of RA production may be involved in the age-related decrease in antigen-specific Treg induction.